Relevant animal model of human lymphoblastic leukaemia/lymphoma--spontaneous T-cell lymphomas in an inbred Sprague-Dawley rat strain (SD/Cub) - Otová, B; Sladká, M; Damoiseaux, J; Panczak, A; Mandys, V; Marinov, I (Folia biologica, 2002)
More than a decade of experimental work in an inbred subline of Sprague-Dawley rats having high incidence of spontaneous T-cell lymphoma/leukaemia is reviewed. Longitudinal follow-up of biological characteristics (growth, survival, haematology) of both multiple cases of primary disease and s.c. passaged lymphomas as well as comparative immunophenotypic and karyotypic studies are concluded. In these T-cell lymphomas (mostly CD4 positive), arising on the same genetic background of the inbred SD strain, the aberrations involving chromosome 11 have been recognized as a typical non-random cytogenetic marker. This unique rat model of lymphoblastic lymphomas/leukaemias, relevant to human pathology, seems to be very suitable for testing different anticancer therapeutic strategies, as it is documented by results of a number of various protocols conducted in our laboratory.
Keywords: Animals; akutní lymfatická leukemie; Aging; lidé; Antineoplastic Agents; protinádorové látky; míra přežití; Immunophenotyping; Rats, Sprague-Dawley; imunofenotypizace; modely nemocí na zvířatech; potkani Sprague-Dawley; stárnutí; Disease Models, Animal; krysa rodu Rattus; akutní T-buněčná leukemie; Survival Rate; Leukemia-Lymphoma, Adult T-Cell; Precursor Cell Lymphoblastic Leukemia-Lymphoma; zvířata; Rats; Humans